Еволюція уявлень про вікову осудність і кримінальну відповідальність дітей - Кузьменко, Олександр Васильович (НТУ "ХПІ", 2016)
У статті досліджується розвиток правової думки України в аспекті уявлень про вікову осудність і кримінальну відповідальність неповнолітніх. Встановлюються соціально-економічні та політичні чинники зазначеного процесу, визначаються його етапи і тенденції. Здійснюється порівняльний аналіз документальних джерел та відповідних правових пам’яток в історії України. Особливістю статті є вивчення процесу становлення ранніх в історичному аспекті уявлень про можливість дитини с певного віку нести кримінальну відповідальність за вчинені злочини.

Rising youth crime in modern conditions make urgent study of the history of development of domestic legislation on criminal liability of minors. The article investigates the development of legal thought in terms of perceptions of age sanity and сriminal responsibility of adolescents. We establish the socio-economic and political factors of this process, defined its stages and trends. The comparative analysis of the documentary sources and the relevant legal sites in the history of Ukraine. A feature article is to study the process of formation in the early historic aspects of ideas about the possibility of a child with a certain age, be held criminally responsible for the crimes committed. The practical significance of the study is that the results can be used to further improve the criminal law in respect of liabili ty for minor offenses committed by them.
The evolution of ideas about the age of responsibility and criminal liability of children
Keywords: злочин; суд; неповнолітні; покарання; заходи впливу; вплив медичний; вплив педагогічний; age sanity; crime; court; measures of influence; medical influence; pedagogical influence